The role of superficial high-frequency ultrasonography in assessing vulvovaginal lesions: A retrospective study - Kakoly Borthakur (WFUMB Ultrasound Open)
Objective: Ultrasound is a well-established imaging modality for assessing the female pelvis and perineum, primarily using convex or transvaginal probes. However, the vulvar region, being superficially located, remains inadequately evaluated by conventional ultrasound techniques. This study aims to explore the efficacy of superficial linear high-frequency ultrasonography, employing a targeted trans-perineal approach, in detecting and characterizing vulvovaginal lesions. Methods: This retrospective study analyzed 61 patients presenting with clinical symptoms of pain or swelling in the vulvar region. Superficial high-resolution linear ultrasound was utilized as the primary diagnostic tool, with convex and intracavitatory probes employed in select cases. The ultrasound findings were correlated with clinical assessments, surgical outcomes, and pathological results. Results: The ultrasound findings demonstrated a diagnostic accuracy of 95 % (CI - 89.5 %). Notably, 78.6 % of patients were treated based solely on ultrasound findings. While some cases underwent further evaluation with Magnetic Resonance Imaging (MRI), the additional findings did not significantly alter management or treatment outcomes. The predominant lesions identified were cystic in nature, originating from the vulva, vagina, or urethra, with most cases being acute inflammatory or infective lesions necessitating urgent medical intervention. Conclusion: This study underscores the potential of ultrasound in the diagnosis and management of vulvar and superficial perineal lesions. The findings support the use of superficial high-frequency ultrasonography as a valuable tool in the morphological assessment of vulvovaginal lesions, facilitating timely diagnosis and treatment. This approach can potentially reduce healthcare costs and improve patient outcomes for those suffering from acute conditions, ultimately leading to improved clinical outcomes.